Sagot :
Answer:
(1 + 3 * 6 - 6 + 1(6)*6)-5 + 3 + 3 = 50/1 = 50
Step-by-step explanation:
1.Multiple: 3 * 6 = 18
2.Add: 1 + the result of step No. 1 = 1 + 18 = 19
3.Subtract: the result of step No. 2 - 6 = 19 - 6 = 13
4.Multiple: 1 * 6 = 6
5.Multiple: the result of step No. 4 * 6 = 6 * 6 = 36
6.Add: the result of step No. 3 + the result of step No. 5 = 13 + 36 = 49
7.Subtract: the result of step No. 6 - 5 = 49 - 5 = 44
8.Add: the result of step No. 7 + 3 = 44 + 3 = 47
9.Add: the result of step No. 8 + 3 = 47 + 3 = 50